2014
DOI: 10.1134/s0021364014030059
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting quantum interference device without Josephson junctions

Abstract: A new type of a superconducting quantum interference device (SQUID) based on a single superconducting loop without Josephson junctions and with asymmetric link-up of current leads is proposed. This SQUID offers advantages in simplicity of fabrication and higher sensitivity of magnetic flux. Magnetic field dependence of the critical current in aluminium rings with asymmetric link-up of current leads has been measured in order to confirm the possibility of making this type of SQUID.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…The overlap of the black and red curves is consistent with the physical symmetry of the system: Reversing the direction of the current and the applied field at the same time should produce no change to the system. both the direction of applied current and the direction of the magnetic field will reproduce the initial untransformed state [15]. We illustrate the symmetry transformation on Device 51215s3, in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overlap of the black and red curves is consistent with the physical symmetry of the system: Reversing the direction of the current and the applied field at the same time should produce no change to the system. both the direction of applied current and the direction of the magnetic field will reproduce the initial untransformed state [15]. We illustrate the symmetry transformation on Device 51215s3, in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nanowire networks [12] and loops [13][14][15][16][17][18][19][20] are qualitatively distinct from conventional Josephson junction and SQUIDS due to the linear nature of the nanowire CPR [13]. In contrast, conventional Josephson junctions obey a sinusoidal CPR.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A few designs of small SQUIDs without Josephson junctions have been proposed, based on mesoscopic superconducting loops7, asymmetric superconducting rings8, inhomogeneous superconductors9, constrictions in the superconducting rim10, interrupted mesoscopic normal loop in contact with two superconducting electrodes11, and a combination of superconducting and metallic contact banks12. SQUIDs without Josephson junctions may offer advantages in simplicity of fabrication, and, under certain conditions, a steeper dependence of the measured quantities on the magnetic flux8. The present study may offer a different approach in designing a SQUID without Josephson junctions by switching a nano-ring with two arms into a SQUID using a large enough bias current.…”
mentioning
confidence: 99%
“…The theory predicts the jump of the critical current with the n change at Φ = (n + 0.5)Φ 0 not only of the double contour interferometer but also, for example, of a superconducting ring with asymmetric link-up of current leads. A simple magnetometer based on the latter prediction was proposed in [20]. But measurements of aluminium ring with asymmetric link-up of current leads have revealed that a smooth change of its critical current is observed at Φ ≈ (n + 0.5)Φ 0 instead of the jump which must be observed due to the change of the quantum number from n to n+1 [21].…”
mentioning
confidence: 99%